On dependence structure of copula-based Markov chains. (10th October 2014) - Longla, Martial
<x content-type="archive" xml:space="preserve">Abstract</x> We consider dependence coefficients for stationary Markov chains. We emphasize on some equivalencies for reversible Markov chains. We improve some known results and provide a necessary condition for Markov chains based on Archimedean copulas to be exponential Ï-mixing. We analyse the example of the Mardia and Frechet copula families using small sets.